2018
DOI: 10.18632/oncotarget.24545
|View full text |Cite
|
Sign up to set email alerts
|

Reduced SMAD2/3 activation independently predicts increased depth of human cutaneous squamous cell carcinoma

Abstract: The incidence of cutaneous squamous cell carcinoma (cSCC) is rising. Whilst the majority are cured surgically, aggressive metastatic cSCC carry a poor prognosis. Inactivating mutations in transforming growth factor beta (TGF-β) receptors have been identified amongst genetic drivers of sporadic tumours and murine models of cSCC, suggesting a tumour suppressor function for TGF-β in normal skin. However, paradoxically, TGF-β acts as a tumour promoter in some murine model systems. Few studies have analysed the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Sensitivity to MEK inhibition was seen across all lines at high concentration, low concentration-response between lines was heterogenous. MEK inhibition may be a basis for molecularly targeted cSCC chemoprevention and therapy.[67]SCCIC18Activated SMAD2/3 was significantly reduced in perilesional cSCC and, to a greater extent, lesional cSCC tissue. Increased tumour thickness inversely correlates with phospho-SMAD presence.…”
Section: Table A1mentioning
confidence: 99%
“…Sensitivity to MEK inhibition was seen across all lines at high concentration, low concentration-response between lines was heterogenous. MEK inhibition may be a basis for molecularly targeted cSCC chemoprevention and therapy.[67]SCCIC18Activated SMAD2/3 was significantly reduced in perilesional cSCC and, to a greater extent, lesional cSCC tissue. Increased tumour thickness inversely correlates with phospho-SMAD presence.…”
Section: Table A1mentioning
confidence: 99%
“…We recently reported that TGF‐β canonical signalling as measured by PO 4 ‐SMAD3 expression was primarily localized to the hair follicle stem cells in normal skin, is active in perilesional and cSCC tissue, and decreased with markers of disease progression 17–19 . We employed the same method using tissue sections from six patients with RDEB cSCC, and detected nuclear localization of PO 4 ‐SMAD3 in all RDEB cSCC samples (representative samples shown in Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Using our published immunohistochemistry protocol 19 for detecting PO 4 ‐SMAD3 (ab52903; Abcam), 4‐μm‐thick cryosections or formalin‐fixed paraffin‐embedded tissue sections were stained and imaged as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations